Dielectric Properties of the Medusae Fossae Formation and Implications for Ice Content. Issue 3 (16th March 2021) - Campbell, Bruce A.; Watters, Thomas R.; Morgan, Gareth A.
Abstract: The extensive Medusae Fossae Formation (MFF) along the dichotomy boundary on Mars has geologic features indicative of wind erosion of low‐density material. There is evidence suggesting a water ice component, but with considerable uncertainty linked to the unknown MFF porosity and compaction behavior. We use SHARAD radar sounder data to estimate the real permittivity and loss tangent of MFF deposits, and compare these to a model for sediment compaction and to the properties of ice in mid‐latitude glaciers. In areas along the margins of Eumenides Dorsum, between Gordii Dorsum and Amazonis Mensa, and in northwest Zephyria Planum, the loss tangent is about 0.001 at 170 m and plateaus at about 0.003 for 310–550 m thickness. The real dielectric constant across the study areas ranges from 2 to 3. We propose that the MFF is a two‐layer deposit, with 300–600 m of fine‐grained, self‐compacting material above up to 2 km of minimally compacting, low‐loss material. The lower unit could be ice‐free and very coarse‐grained, but we see no evidence of extensive sand exposed by erosion. The lower layer might instead be ice‐rich and protected from sublimation by the dry cover. The volume of cover relative to a high ice content in the lower layer implies hybrid MFF formation as glacial or polar layered deposits capped by a dry, perhaps pyroclastic ash, component. Plain Language Summary: The Medusae Fossae Formation (MFF) on Mars covers a vast area along the boundary between the rugged southern highlands and the smooth northern plains. While the MFF appears to be thick sediments or volcanic ash slowly eroding in the martian winds, how this material was emplaced remains mysterious. Most intriguing is evidence suggesting that some areas of the MFF may contain water ice. In this work we use sounding radar data from the SHARAD instrument on the Mars Reconnaissance Orbiter to probe up to 600 m below the surface and measure the electrical properties of the MFF material. The results suggest that the shallow parts of the MFF deposits are very porous and compress readily under their own weight. To match deeper probing by the Mars Advanced Radar for Subsurface and Ionosphere Sounding instrument on Mars Express requires a second layer of either vast porous deposits or ice‐rich material protected from sublimation by the dry sediments. Key Points: The Medusae Fossae Formation is a 5, 000‐km band of thick material along the edge of the martian highlands SHARAD measurements show an increase in electrical loss as the first few hundred meters of material compact Deposits of ice buried by sediments may be required to explain the lack of further increase in dielectric loss beyond 300–600 m thickness